PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN SERANG - Ely Rohayani Lestari; Khaeruman Khaeruman; Edi Muhammad Abduh (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the influence of work motivation and work environment on employee work productivity at the National Unity and Politics Agency of Serang Regency. The method used is a quantitative approach with an associative type of research, where data was collected through questionnaires from 31 respondents. Multiple linear regression test was used to test the research hypothesis. The research results show that work motivation has a significant effect on employee work productivity. The work environment has also been proven to have a positive influence on work productivity. Simultaneously, work motivation and work environment have a significant influence on employee work productivity. These findings indicate that increasing motivation and improving the work environment can increase employee productivity in the organization.